Historiographical review of the intellectual life of iran in the late хix-1st half of the xx century - Rakhimova, K.; Batyrkhan, B. (Journal of Oriental Studies, 2022)
The investigation is devoted to the analysis of the sources related the topic of the scientific research. In the introduction, the author focuses on the events of the 19-th century and comments on the political situation in the Iranian country. The article reviews and informs about the problems and events that have arisen in the country as a result of these political processes. In the main part of the article, the sources under the topic are divided into three groups for investigation. It examines the research studies published at different times and focuses on their original value. Particularly special attention is paid to works on the history of Iran, displaying the relief of events “from time immemorial to the present day” as valuable sources of the research under investigation. The next most important source highlighted in the article is the study of Iranian researchers on the events of that period. In conclusion, the author says that in the future, these sources will be studied in the research work, depending on the level of source study significance, and a historical comparative analysis will be carried out. The article provides a historiographic comparative analysis of the sources. The aim of the research work is to determine the bibliographic base of the research work. The scientific and practical significance of the article lies in the identification of source materials and disclosure of the source value of future research work. In the research work, guided by the conclusions obtained in the article, a plan of the future work program is drawn up, which will be supplemented in the course of the research.